2020
DOI: 10.1002/bit.27561
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the caspase 8‐associated protein 2 gene improves recombinant protein expression in HEK293 cells through up‐regulation of the cyclin‐dependent kinase inhibitor 2A gene

Abstract: Cell lines used in bioproduction are routinely engineered to improve their production efficiency. Numerous strategies, such as random mutagenesis, RNA interference screens, and transcriptome analyses have been employed to identify effective engineering targets. A genome-wide small interfering RNA screen previously identified the CASP8AP2 gene as a potential engineering target for improved expression of recombinant protein in the HEK293 cell line. Here, we validate the CASP8AP2 gene as an engineering target in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…The higher JRed expression (1.5-fold) in CHO-KO cells compared to CHO-K1 cells also confirmed the primary findings. In line with this evidence, Abaandou et al reported that the caspase 8‐associated protein 2 (CASP8AP2) gene silencing improved recombinant protein expression in HEK293 cells by inducing cell cycle arrest in G0/G1 checkpoint [ 34 ]. They demonstrated that silencing CASP8AP2 lead to the enhancement of luciferase and SEAP production by up to 7- and 2.5-fold respectively.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The higher JRed expression (1.5-fold) in CHO-KO cells compared to CHO-K1 cells also confirmed the primary findings. In line with this evidence, Abaandou et al reported that the caspase 8‐associated protein 2 (CASP8AP2) gene silencing improved recombinant protein expression in HEK293 cells by inducing cell cycle arrest in G0/G1 checkpoint [ 34 ]. They demonstrated that silencing CASP8AP2 lead to the enhancement of luciferase and SEAP production by up to 7- and 2.5-fold respectively.…”
Section: Discussionmentioning
confidence: 97%
“…CHO-KO and native CHO-K1 cells were plated in 96-well plates with a concentration of 5 × 10 3 per well in quintuplicate. Cells were incubated for 24, 48, 72 and 96 h [ 34 ] and after that doubling time of cells was identified by using cell counter. For cell viability assay the medium from each well was entirely removed and replaced with 100 µL of fresh serum-free culture medium containing 5 mg/mL MTT solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The knockdown of INTS1, HNRHPC, OAZ, CASP8AP2 and PPP2R1A consistently improved the expression of at least two reporter proteins tested by up to 72% [ 115 ]. In follow-up studies, the CRISPR/Cas9 knockout of the ornithine decarboxylase antizyme1 ( OAZ1 ) resulted in a 5-fold improvement in luciferase production and a 2.5-fold improvement in transient specific secreted alkaline phosphatase (SEAP) production [ 116 ], and knockout of the caspase 8 associated protein 2 ( CASP8AP2 ) gene resulted in a 7-fold increase in specific luciferase production and a 2.4-fold increase in transient specific SEAP production [ 117 ].…”
Section: Strain/genetic Engineering For Enhanced Recombinant Protein Expression In the Hek293 Cell Linementioning
confidence: 99%